2012
DOI: 10.1002/jat.2733
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the progression of crystalline silica‐induced pulmonary toxicity in rats

Abstract: Identification of molecular target(s) and mechanism(s) of silica‐induced pulmonary toxicity is important for the intervention and/or prevention of diseases associated with exposure to silica. Rats were exposed to crystalline silica by inhalation (15 mg m−3, 6 h per day, 5 days) and global gene expression profile was determined in the lungs by microarray analysis at 1, 2, 4, 8 and 16 weeks following termination of silica exposure. The number of significantly differentially expressed genes (>1.5‐fold change and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 60 publications
(66 reference statements)
1
35
0
Order By: Relevance
“…diseases and even future treatment options. 15,61 The use of biomarkers, together with more sensitive imaging methods, may allow the design of algorithms that can be implemented to benefit early diagnosis of silicosis.…”
mentioning
confidence: 99%
“…diseases and even future treatment options. 15,61 The use of biomarkers, together with more sensitive imaging methods, may allow the design of algorithms that can be implemented to benefit early diagnosis of silicosis.…”
mentioning
confidence: 99%
“…Furthermore, setting scientifically based limit values is complicated, owing to the difficulties in interpreting heterogeneous experimental and epidemiological findings (Chen et al 2001a;OEHHA 2005;Zhuang et al 2001). Despite much recent progress in our understanding of source attribution, emission factors, and regulation of silica (Chen et al 2012;Rong et al 2013;Sellamuthu et al 2013), current risk assessment models based on parameterization of laboratory experiments cannot fully explain the magnitude of silica-induced pulmonary disease risk. Furthermore, the silicosis is rated the most prevalent occupational disease among all industries in Taiwan (Shih et al 2008).…”
Section: Responsible Editor: Marcus Schulzmentioning
confidence: 95%
“…Rong et al (2013) and Sellamuthu et al (2013) indicated that the biological effects of silica included direct ones on several pathways such as inflammatory responses, cell-tocell signaling and interaction, cellular movement that lead to inflammatory and respiratory diseases, and finally cancer. Porter et al (2006) and Shen et al (2001) indicated that silica could produce reactive oxygen species (ROS) and lipid peroxidation to disrupt lipid rafts and active protein tyrosine kinase, resulting in the subsequent translocation of transcription factors.…”
Section: Responsible Editor: Marcus Schulzmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome‐wide microarray studies have previously demonstrated that ALI induces coordinated changes in the expression of hundreds of genes . We hypothesized that analyzing a representative subset of these previously described ALI‐related transcripts would allow for more precise, objective, and mechanistic evaluation of lung tissue injury and repair before, during, and after EVLP.…”
Section: Introductionmentioning
confidence: 99%